Oral Health Among Tobacco-Chewers in an Urban Area of Karachi - Farzeen Tanwir; Amna Tariq (Journal of the Dow University of Health Sciences, 2011)
Oral diseases like periodontal disease, dental disease and related oral mucosal lesions are major public health concerns worldwide although there has been an improvement in oral health but the problem still persists on a global scale.